Moonlighting-A Need of the Day - jain, Puja (Gyan Management Journal, 2013)
Moonlighting has become a need in this fast and competitive life where means are limited but wish list is never ending. Utilizing latent potential and converting it into money and get contentment is not wrong but at the same time care should be taken that it does not put you and your family life in peril. Following certain measures can not only fulfill your need but help restore balance in life.